The Efficacy of Exposure and Response Prevention for Geriatric Obsessive Compulsive Disorder: A Clinical Case Illustration - Jones, Mairwen K.; Wootton, Bethany M.; Vaccaro, Lisa D. (Case Reports in Psychiatry, 2012)
Obsessive compulsive disorder (OCD) is one of the most frequently occurring psychiatric conditions in older adults. While exposure and response prevention (ERP) is considered the most effective psychological treatment for children and adults with OCD, research investigating its effectiveness for older adults is scarce. This clinical case study investigates the effectiveness of ERP in an 80-year-old man with a 65-year history of OCD. The client received 14 individual, 50-minute ERP treatment sessions. Clinician-based Y-BOCS scores reduced by 65% from 20 (moderate) at pretreatment to 7 (subclinical) at 7-month posttreatment followup. OCI-R total scores reduced by 45% from 38 at baseline to 21 at 7-month follow-up. Despite his long history of the disorder, ERP was effective and well tolerated. The application of ERP for older adults with OCD, including age-specific modifications that may be required for this treatment approach, is discussed.